2010
DOI: 10.5398/medpet.2010.33.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharides in Milk: Their Benefits and Future Utilization

Abstract: The percentage of carbohydrate in the milk/colostrum of the mammalian is range from trace to over 10%, of which disaccharide lactose (Gal(β1-4)Glc) is usually constitutes the major part. Apart from the lactose (Gal(β1-4)Glc; Gal, D-galactose; Glc, D-glucose), the rest of carbohydrate components is composed of variety of sugars, commonly named as milk oligosaccharides. Human mature milk and colostrum contain 12 ~ 13 g/l and 22 ~ 24 g/l of oligosaccharides, respectively. In contrast, bovine colostrum contains mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…In addition, a direct comparison between these 2 species is unwarranted due to differences in genetics, production, and nutrition. Although little is known about how parity number in bovine animals may affect OS concentration and yield, OS synthesis in the mammary gland is known to occur by the action of a glycosyltransferase (e.g., sialyltransferase) specific to each molecule (Urashima and Taufik, 2011), which takes place in different compartments of the cell, including the cytosol, nucleus, and Golgi apparatus (Wickramasinghe et al, 2011;Petrosyan et al, 2012). Wickramasinghe et al (2011) demonstrated that 92 glycosylated-related genes were involved in OS metabolism pathways in bovine somatic cells, which are representative of mammary gland tissue (Cánovas et al, 2014), at d 15 and 250 of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a direct comparison between these 2 species is unwarranted due to differences in genetics, production, and nutrition. Although little is known about how parity number in bovine animals may affect OS concentration and yield, OS synthesis in the mammary gland is known to occur by the action of a glycosyltransferase (e.g., sialyltransferase) specific to each molecule (Urashima and Taufik, 2011), which takes place in different compartments of the cell, including the cytosol, nucleus, and Golgi apparatus (Wickramasinghe et al, 2011;Petrosyan et al, 2012). Wickramasinghe et al (2011) demonstrated that 92 glycosylated-related genes were involved in OS metabolism pathways in bovine somatic cells, which are representative of mammary gland tissue (Cánovas et al, 2014), at d 15 and 250 of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…Cows' milk-based infant formulas are widely used, but goats' milk-based products are becoming increasingly popular as goats' milk is considered to be more similar to human milk compared with cows' milk. This includes higher levels of oligosaccharides in goats' milk relative to milk of other mammalian species (2) and lower levels of α-S1 casein (3) . Goats' milk is also reported to exhibit significant homology in lactoferrin N-glycans with human milk (4) .…”
mentioning
confidence: 99%
“…Quite frequently lactose is attached with sialic acid residues to form trisaccharides also called as short‐chain milk oligosaccharides. Sialyted lactose could be extended by more N ‐acetylglucosamine repeats up to as long as 15 residues to form complex oligosaccharides (Urashima and Taufik 2010).…”
Section: Human Milk Oligosaccharidesmentioning
confidence: 99%